Frequency of Leakage in Primary Repair of Acute Colonic Injury (Medical Forum Monthly, 2022)
Objective: To determine the frequency of Leakage in primary repair of acute colonic injury patients admitted in Surgical B Ward, Ayub Teaching Hospital, Abbottabad.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, Ayub Teaching Hospital, Abbottabad from January 2022 to June 2022.Materials and Methods: Eighty-nine patients who attending the surgery department for any type of trauma, ages ranging from 22 to 50 years of either gender were enrolled. After patient selection, their history, examination, investigations (complete blood count, renal functions tests, serum electrolytes, liver functions examinations, screening tests for hepatitis C, hepatitis B, abdominal ultrasound, chest x-ray), surgery was carried out.Results: The mean age group of subjects the patients was 36.69±8.325. The age group ranged between 22 and 50 years, and the frequency of gender of the subjects, 63(70.8%), was male, and 26(29.2%) were female. In the frequency of the type of trauma, patients presented with a firearm injury to the abdomen with colon were 38(42.7%), with blunt abdominal trauma were 20(22.5%), and stab wound abdomen was 20(22.5%). In contrast, other types of trauma e.g. fall from the roof and RTA etc. were 1 to 4%. In the frequency of anastomotic Leakage, 21(23.6%) patients were found to have a postoperative complication, i.e. anastomotic Leakage, while the remaining 68(76.4%) had no leakage.Conclusion: Colonic wounds continue to be a clinical issue for trauma surgeons that are both prevalent and occasionally difficult. Those improvements in both death rates and morbidity amply illustrate the extraordinary advancement in caring for these wounds.